Mitochondrial Oxidative Stress-Associated Mechanisms in the Development of Metabolic Dysfunction-Associated Steatotic Liver Disease - Yang, Juan; Zhang, Jiahui; Zhang, Le; Yang, Zhenshan ; 0000-0001-6987-9947 (Biocell, 2025)
With the prevalence of obesity, metabolic dysfunction-associated steatotic liver disease (MASLD) has become the most common chronic liver disease worldwide and can cause a series of serious complications. The pathogenesis of MASLD is complex, characterized by oxidative stress, impaired mitochondrial function and lipid metabolism, and cellular inflammation. Mitochondrial biology and function are central to the physiology of the liver. It has been suggested that mitochondrial oxidative stress plays a crucial role in MASLD progression. Excessive oxidative stress response is an important trigger for the occurrence and development of MASLD. In this review, we aim to focus on the recent advances in understanding mitochondrial oxidative stress-related mechanisms in the progression of MASLD. The in-depth elaboration of its related mechanisms is hoped to help find effective methods for treating MASLD.
Keywords: ER-mitochondria association; MASLD; mitochondrial dysfunction; mitochondrial quality control; Oxidative stress